Does the primary site of colorectal cancer impact outcomes for patients with metastatic disease?. Issue 6 (6th November 2014) - Price, Timothy J.; Beeke, Carol; Ullah, Shahid; Padbury, Robert; Maddern, Guy; Roder, David; Townsend, Amanda R.; Moore, James; Roy, Amitesh; Tomita, Yoko; Karapetis, Christos
<x xml:space="preserve">Abstract</x> BACKGROUND Previous reports have described differences in biology and outcome for colorectal cancer based on whether the primary is right or left sided. Further division by right, left, and rectum or even exact primary site has also been explored. Possible differences in response to biological agents have also been reported based on side of primary lesion. METHODS We explored the South Australian registry for metastatic colorectal cancer to assess if there were any differences in patient characteristics, prognostic markers, and treatment received and outcomes based on whether the primary was right or left sided. We also explored if differences exist based on left colon and rectum and by exact primary site. RESULTS Two thousand nine hundred seventy‐two patients were analyzed. Thirty‐five percent had a right‐sided primary. The median overall survival for the entire group right versus left was 9.6 versus 20.3 months (P < .001). Multivariate analysis confirmed side of primary as an independent prognostic factor. For the group that had active therapy, defined as chemotherapy (± metastasis resection), median overall survival was right, 18.2 months; and left, 29.4 months (P < .001). Importantly, we found no suggestion of major differences if left side was divided by left colon and rectum, and trends by individual site still supported a left and right division. CONCLUSIONS Patients with a right‐sided primary have more negative prognostic factors and indeed have inferior outcomes compared with those with a left‐sided primary. Our data with further breakdown by exact site still favor a simple left‐versus‐right division moving forward for metastatic colorectal cancer. Cancer 2015;121:830–835. © 2014 American Cancer Society.